An adaptive strategy for control of a hybrid electrical system-Modelling and simulation of a parallel hybrid system for heavy vehicles - Andersson, Annika (My University, 2008)
The objective of this thesis is to develop and implement an energy return strategy for a parallel hybrid system in a heavy vehicle model. The energy return strategy should, with the help of adaption based on how often and how much energy that is cycled throw the system, try to maximize the energy returned to the drive line. This is done by lowering the power take out and thereby increasing the efficiency of the battery and lowering the heat generated in it, but also making sure there is enough room in the battery for the next braking. The work also contained modelling of the hybrid systems components for implementation in the existing vehicle model. The strategy implemented shows the ability to adapt and maintain centered distribution of the state of charge level, the energy return value is not maximum for the adaption compared to constant values of the same parameter. The interaction between the adaptive parameter and the other parameters in the strategy needs to be further investigated as well as the efficiency of the system in different operating point.
Keywords: Elkraftteknik; Electric power engineering